Konsep Time Value of Money dan Economic Value of Time dalam Ekonomi Islam: Studi Perbandingan dan Implikasinya - Assiddiqie, Muhammad Jimly (Maliki Interdisciplinary Journal, 2026)
The concept of Time Value of Money (TVM) is a cornerstone in conventional finance, stating that the value of money today is greater than the same amount in the future due to inflation, consumption preference, and uncertainty. However, from an Islamic economic perspective, this concept is considered contradictory to the prohibition of riba (usury), as it is seen as deriving profit from time without real economic activity. This paper aims to analyze the fundamental differences between TVM in conventional economics and its Islamic alternative, the Economic Value of Time (EVT). This research employs a literature study method with a descriptive-comparative approach. The analysis reveals that Islam rejects TVM because it views money solely as a medium of exchange and a unit of account, not as a commodity that can reproduce itself. As an alternative, Islam introduces EVT, which emphasizes the economic value derived from utilizing time for productive activities and real transactions. Profit in the Islamic system is generated from tangible economic activities, such as asset sales (Murabahah) or diminishing partnership (Musyarakah Mutanaqisah), not from interest on money loans. The implementation of this concept can be observed in sharia financing products in Indonesia, such as those offered by Bank Syariah Indonesia. This study concludes that this paradigm difference has profound implications for the economic system, where Islamic economics prioritizes justice, risk-sharing, and the circulation of money for collective welfare, contrasting with the interest-based growth orientation in the conventional system.